2017
DOI: 10.3184/174751917x15045169836217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Biological Evaluation of Novel 2-Phenylthiazole Derivatives as Multi-Targeting Agents to Treat Alzheimer's Disease

Abstract: Three novel 2-phenylthiazole derivatives were synthesised and characterised by spectroscopic techniques. The structure of the synthesised compounds was unambiguously confirmed by a single-crystal X-ray diffraction analysis of ethyl 2-(4-{[5-(4-benzylpiperidin-1-yl)pentyl]oxy}phenyl)thiazole-4-carboxylate. All of the compounds presented good cholinesterase-inhibition activities and ethyl 2-(4-{[5-(4-benzylpiperidin-1-yl)pentyl]oxy}phenyl)thiazole-4-carboxylate showed the best acetylcholinesterase-inhibition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…[4][5][6] We have previously synthesised a series of 2-phenylthiazole derivatives and found that these derivatives possess AChE-and BuChE-inhibiton activities. 7,8 In this study, three novel 2-phenylthiazole derivatives were synthesised and characterised by NMR and single-crystal X-ray diffraction analysis. The role of intermolecular interactions in these compounds was analysed through single-crystal structure studies.…”
mentioning
confidence: 99%
“…[4][5][6] We have previously synthesised a series of 2-phenylthiazole derivatives and found that these derivatives possess AChE-and BuChE-inhibiton activities. 7,8 In this study, three novel 2-phenylthiazole derivatives were synthesised and characterised by NMR and single-crystal X-ray diffraction analysis. The role of intermolecular interactions in these compounds was analysed through single-crystal structure studies.…”
mentioning
confidence: 99%